Biomonitoring of heavy metals in the west coastal waters of Peninsular Malaysia using the green-lipped mussel perna viridis: Present status and what next? - Yap, Chee Kong; Ismail, Ahmad; Tan, Soon Guan (Universiti Putra Malaysia Press, 2004)
This paper aims to review the papers published using Perna viridis as a biomonitoring agent of heavy metals in this region and particularly from Malaysia and to discuss the existing knowledge. Further research which will enhance our understanding and increase our knowledge on heavy metal ecotoxicology in Malaysia by using P. viridis is also suggested. This can be part of Mussel Watch monitoring program in this region. The work in establishing P. viridis for the biomonitoring of heavy metals, which is fundamentally based on the recommended criteria for a good biomonitoring agent, can be applied in other mollusks species.